Influence of Sepiolite Addition Methods and Contents on Physical Properties of Natural Rubber Composites - Nabil Hayeemasae; Ajaman Adair; Mohamad Syahmie Mohamad Rasidi; Patiwarada Jitsopin; Abdulhakim Masa (Science and Technology Indonesia, 2022)
The influence of sepiolite loadings (1-10 phr) and sepiolite addition procedures (mill and latex mixing approaches) on properties improvement of natural rubber composites was investigated. The viscosity, curing behavior, and tensile test were used to assess the property changes whereas the rubber-filler interactions was confirmed by using stress relaxation, swelling, Mooney-Rivlin and rheological methods. It was found that the characteristics of rubber composites influenced by both mixing methods and filler contents. Comparing between two different mixing methods, the slower stress relaxation rate and less swelling capability were achieved from mill mixing technique. This method also lowered the strain where the upturn of stress was occurred as suggested by Mooney-Rivlin plot. The greater properties enhancement of composites was obtained from milling method because of the better rubber-filler interactions, probably as a result of the nature of filler used. The greatest tensile strength improvement was achieved at 1 phr sepiolite loading where the smallest damping characteristics (tan ????) indicating the highest elastic behavior were obtained as revealed by rheological measurements. The simplicity of production and shortened step of milling procedure would be more favorable than the latex mixing approach for fabrication sepiolite filled rubber composites.